Performance evaluation of a foot interface to operate a robot arm - Huang, Yanpei (2020)
We developed a foot interface enabling an operator to control a robotic arm with four degrees of freedom in continuous direction and speed, for operating one of the multiple tools required during robot-aided surgery. In this letter, we first test whether this pedal interface can be used to carry out complex manipulation as is required in surgery. Second, we compare the performance of ten naive operators using this new interface and a traditional button interface providing axis-by-axis constant-speed control. Testing is carried out on geometrically complex path-following tasks similar to laparoscopic training. Movement precision, time and smoothness are analyzed. The results demonstrate that the continuous pedal interface can be used to control a robot in complex motion tasks. The subjects kept the average error rate at a low level of around 2.6% with both interfaces, but the pedal interface resulted in about 30% faster operation and 60% smoother movement, which indicates improved efficiency and user experience as compared with the button interface. A questionnaire shows that controlling the robot with the pedal interface was more intuitive, comfortable, and less tiring than with the button interface.